Comparison of nutritional effectiveness and complication rate between early nasojejunal and nasogastric tube feeding in patients with an intracerebral hemorrhage. (September 2022) - Ling, Cong; Hu, Xiling; Chen, Chuan; Luo, Lun; Cai, Meiqin; Liang, Chaofeng; Wang, Hui; Guo, Ying
Highlights: We compared the effect of nasojejunal and nasogastric nutrition in IH patients. Enteral nutrition affects nutritional status and is associated with complications. Early nasojejunal nutrition was associated with improved nutritional effectiveness. Abstract: Background: This study aimed to compare nutritional effectiveness and complication rate between early nasojejunal and nasogastric tube feeding in patients with an intracerebral hemorrhage. Methods: This was a retrospective study. Eighty patients with an intracerebral hemorrhage were divided into a nasojejunal and a nasogastric tube feeding group. Feeding tubes were placed within 6 h after admission, and enteral feeding began within 2 h after tube placement. The nutritional status and complication rate of the 2 groups were compared before and 2 and 4 weeks after beginning feeding. Results: Serum prealbumin, serum albumin, and hemoglobin levels were significantly higher in the nasojejunal tube feeding group than in the nasogastric tube feeding group at 2 and 4 weeks after beginning feeding (all, p < 0.05). The incidence of gastric retention, pulmonary aspiration, and pneumonia were lower in the early nasojejunal tube feeding group than in the early nasogastric tube feeding group (all, p < 0.05). There was no significant difference in the incidence of diarrhea between the 2 groups. Conclusion: Compared with early nasogastric feeding, early nasojejunal feeding provides better nutritional effectiveness and a lower incidence of gastric retention, pulmonary aspiration, and pneumonia in patients with an intracerebral hemorrhage.